Structural basis for substrate specificity of l‐methionine decarboxylase. (21st January 2021) - Okawa, Atsushi; Shiba, Tomoo; Hayashi, Masaya; Onoue, Yuki; Murota, Masaki; Sato, Dan; Inagaki, Junko; Tamura, Takashi; Harada, Shigeharu; Inagaki, Kenji
Abstract: l ‐ Methionine decarboxylase (MetDC) from Streptomyces sp. 590 is a vitamin B6 ‐dependent enzyme and catalyzes the non‐oxidative decarboxylation of l ‐ methionine to produce 3‐methylthiopropylamine and carbon dioxide. We present here the crystal structures of the ligand‐free form of MetDC and of several enzymatic reaction intermediates. Group II amino acid decarboxylases have many residues in common around the active site but the residues surrounding the side chain of the substrate differ. Based on information obtained from the crystal structure, and mutational and biochemical experiments, we propose a key role for Gln64 in determining the substrate specificity of MetDC, and for Tyr421 as the acid catalyst that participates in protonation after the decarboxylation reaction.